A Systematic Review of “Helicopter Parenting” and Its Relationship With Anxiety and Depression - Vigdal, Julia Schønning; Brønnick, Kolbjørn Kallesten (Frontiers in Psychology, 2022)
Background: Emerging evidence suggests that overprotective and controlling parenting, often referred to as ‘helicopter parenting’ may have negative implications on the child’s mental health such as anxiety and depression. However, no systematic review on the topic exists. Objective: Conducting a systematic review to identify all studies where the relationship between helicopter parenting and symptoms of anxiety and/or depression have been investigated. Method: A systematic literature search conducted the 3rd of November 2021 yielded 38 eligible studies. Since helicopter parenting is a fairly new construct, this review considered parental control and overprotective parenting to be dimensions of helicopter parenting and thus, eligible for the study. Study quality was assessed in accordance with Campbells Validity Typology. Results: The majority of the studies included in this review found a direct relationship between helicopter parenting and symptoms of anxiety and depression. However, validity problems undermine these findings with regarding to assessing the causal relationship between helicopter parenting and these symptoms. There were no longitudinal studies of sufficient quality to determine if helicopter parenting precedes the outcome of anxiety and depression. Conclusion: Even though the majority of the studies included in this systematic review found a relationship between helicopter parenting and anxiety and depression, the evidence for this relationship is insufficient and must be investigated further. Findings suggest that it is important to include both maternal and paternal parenting style in future studies they could affect the outcome of anxiety and depression differently. Systematic review registration: PROSPERO 2020 CRD42020167465